Algorithms and Computation 21st International Symposium, ISAAC 2010, Jeju, Korea, December 15-17, 2010, Proceedings, Part II - Cheong, Otfried; Chwa, Kyung-Yong.; Park, Kunsoo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 21st International Symposium on Algorithms and Computation, ISAAC 2010, held in Jeju, South Korea in December 2010. The 77 revised full papers presented were carefully reviewed and selected from 182 submissions for inclusion in the book. This volume contains topics such as approximation algorithm; complexity; data structure and algorithm; combinatorial optimization; graph algorithm; computational geometry; graph coloring; fixed parameter tractability; optimization; online algorithm; and scheduling.
Session 6A. Data Structure and Algorithm II -- D2-Tree: A New Overlay with Deterministic Bounds -- Efficient Indexes for the Positional Pattern Matching Problem and Two Related Problems over Small Alphabets -- Dynamic Range Reporting in External Memory -- A Cache-Oblivious Implicit Dictionary with the Working Set Property -- Session 6B. Graph Algorithm II -- The (p,q)-total Labeling Problem for Trees -- Drawing a Tree as a Minimum Spanning Tree Approximation -- k-cyclic Orientations of Graphs -- Improved Bounds on the Planar Branchwidth with Respect to the Largest Grid Minor Size -- Session 7A. Computational Geometry II -- Maximum Overlap of Convex Polytopes under Translation -- Approximate Shortest Homotopic Paths in Weighted Regions -- Spanning Ratio and Maximum Detour of Rectilinear Paths in the L 1 Plane -- Session 7B. Graph Coloring II -- Approximation and Hardness Results for the Maximum Edge q-coloring Problem -- 3-Colouring AT-Free Graphs in Polynomial Time -- On Coloring Graphs without Induced Forests -- Session 8A. Approximation Algorithm II -- On the Approximability of the Maximum Interval Constrained Coloring Problem -- Approximability of Constrained LCS -- Approximation Algorithms for the Multi-Vehicle Scheduling Problem -- On Greedy Algorithms for Decision Trees -- Session 8B. Online Algorithm -- Single and Multiple Device DSA Problem, Complexities and Online Algorithms -- The Onion Diagram: A Voronoi-Like Tessellation of a Planar Line Space and Its Applications -- Improved Online Algorithms for 1-Space Bounded 2-Dimensional Bin Packing -- On the Continuous CNN Problem -- Session 9A. Scheduling -- Policies for Periodic Packet Routing -- Increasing Speed Scheduling and Flow Scheduling -- A Tighter Analysis of Work Stealing -- Approximating the Traveling Tournament Problem with Maximum Tour Length 2 -- Session 9B. Data Structure and Algorithm III -- Alphabet Partitioning for Compressed Rank/Select and Applications -- Entropy-Bounded Representation of Point Grids -- Identifying Approximate Palindromes in Run-Length Encoded Strings -- Session 10A. Graph Algorithm III -- Minimum Cost Partitions of Trees with Supply and Demand -- Computing the (t,k)-Diagnosability of Component-Composition Graphs and Its Application -- Why Depth-First Search Efficiently Identifies Two and Three-Connected Graphs -- Beyond Good Shapes: Diffusion-Based Graph Partitioning Is Relaxed Cut Optimization -- Induced Subgraph Isomorphism on Interval and Proper Interval Graphs -- Session 10B. Computational Geometry III -- Testing Simultaneous Planarity When the Common Graph Is 2-Connected -- Computing the Discrete Fréchet Distance with Imprecise Input -- Connectivity Graphs of Uncertainty Regions -- ?/2-Angle Yao Graphs Are Spanners -- Identifying Shapes Using Self-assembly.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Computer software; Electronic data processing; Computational complexity; Computer graphics; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Computer Communication Networks; Computer Graphics; Data Structures; Numeric Computing